Ionic Liquids in Chemical Engineering - Werner, Sebastian; Haumann, Marco; Wasserscheid, Peter (Annual Review of Chemical and Biomolecular Engineering, 2010)
The development of engineering applications with ionic liquids stretches back to the mid-1990s when the first examples of continuous catalytic processes using ionic liquids and the first studies of ionic liquid–based extractions were published. Ever since, the use of ionic liquids has seen tremendous progress in many fields of chemistry and engineering, and the first commercial applications have been reported. The main driver for ionic liquid engineering applications is to make practical use of their unique property profiles, which are the result of a complex interplay of coulombic, hydrogen bonding and van der Waals interactions. Remarkably, many ionic liquid properties can be tuned in a wide range by structural modifications at their cation and anion. This review highlights specific examples of ionic liquid applications in catalysis and in separation technologies. Additionally, the application of ionic liquids as working fluids in process machines is introduced.